Information Technology for Manufacturing Systems III - Wei Deng; Qi Luo (Trans Tech Publications Ltd, 2012)
Selected, peer reviewed papers from the 2012 3rd International Conference on Information Technology for Manufacturing Systems (ITMS 2012), September 8-9, 2012, Qingdao, China